Stabilization of bromthymol blue colour in lecithin-sphingomyelin ratio determinations in amniotic fluid. Issue 10 (October 1976) - Andrews, A G; Horacek, I; Betheras, F R
Abstract : Amniotic fluid lecithin and sphingomyelin areas after extraction and chromatography are rendered permanently visible by the use of bromthymol blue dye buffered to a pH of 11-3.